Cần dậy học những ngoại ngữ nào trong trường phổ thông Việt Nam - Bùi, Hiền (H. : ĐHQGHN, 2017)
In this article the author presents the actual sta te of teaching and learning foreign languages at school in Vietnam. In his opinion, English is a compulsory subject in our national educational system. Other foreign languages, such as French, Russian and Chinese are considered as a second foreign languages. This policy is not suitable for our national interest. He gives some advices for the administrators.